Genshin Impact Game Character Selection Using Weighted Product - Mubarok, Sulton; Fitri, Zilvanhisna Emka; Imron, Arizal Mujibtamala Nanda (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
The recurring problem among Genshin Impact players in choosing characters, especially for new players, is a common issue. Therefore, this study aims to develop a decision support system to assist players in selecting characters using the weighted product method. The study was conducted by collecting data on the available characters in Genshin Impact and evaluating relevant criteria such as character rarity, role, weapon, and element. There are 52 characters or alternatives used in this study. The weighted product method was used to determine the relative weights of each criterion and then used to calculate the value of each character. In conclusion, the implementation of the weighted product method has been successfully carried out based on the three main steps, which are determining the weight of criteria, normalizing alternatives, and determining the preference of each alternative. From the results of the system testing that has been conducted by 25 users, a percentage of 84% was obtained based on user satisfaction with the decision support system for character selection in the Genshin Impact game. 9 respondents chose the option